Efikasi Diri Anak Usia 6-18 Tahun Yang Mengalami Thalasemia - Stella Pramasita; Lina Dewi Anggraeni (Fakultas Keperawatan Universitas Andalas, 2020)
Thalassemia patient should undergo a repeated treatment, so it causes side effects on his health both physically and psychologically.The most common psychological problem suffered by the patient is the decreasing of self efficacy which affects the attitude and mindset of children with thalassemia.The purpose of the research is to find out the 6-18 years old children self efficacy portrayal with thalassemia on hospital X, West Jakarta. The research design is using quantitative descriptive and cross sectional approach and questionnaire with interview as the instrument. The sampling technique used is total sampling with the number of sample is 50 children, conducted on January 2019. Data analysis using shapiro wilk normality test and frequency distribution test. The result of the research shows that 62% including 6-12 years with 60% female sex, respondents who underwent therapy <10 years as much as 52% with early age diagnosed at <1 year as much as 38%. Self efficacy is high in the 13-18 year age group as much as 63.2%, self-efficacy on the general aspects in the 6-12 year age group (58.1%) and 13-18 years old (57.9%) are categorized good, self efficacy on the aspect of strength in the 6-12 year age group (74,2%) and 13-18 year old (73,7%) are categorized good and a high self efficacy on the aspect of level in the 13-18 year age group as much as 63,2%. It is recommended that children with thalassemia can control their self efficacy every day as an effort to maintain their health.